Urban-rural differences in the prevalence and influencing factors of insomnia: a cross-sectional study in Foshan, China - Chu, Zhaosong; Xie, Jianling; Liu, Rui; Ou, Liqin; Lan, Zheng; Liang, Jiaquan; Xie, Guojun (Frontiers in Psychiatry, 2025)
ObjectiveInsomnia is a common sleep disorder that affects quality of life and varies significantly across populations. In China, the urban-rural divide is notable, but differences in insomnia prevalence and influencing factors between these groups remain unclear. Using Foshan as a case study, this research aims to identify these differences to develop targeted interventions for improving sleep quality.MethodsData were obtained from the 2022 Foshan City Residents’ Mental Health Survey, which included 9,044 adult participants (4,546 urban and 4,498 rural residents). Insomnia was assessed using the Insomnia Severity Index, with participants scoring ≥ 8 classified as the insomnia group. Chi-square tests and logistic regression analyses were used to explore urban-rural differences in insomnia prevalence and influencing factors.ResultsThe prevalence of insomnia in Foshan was 18.37%. Urban residents exhibited a significantly higher insomnia rate (19.73%) compared to rural residents (16.99%). Logistic regression analysis indicated that among urban residents, being unmarried, widowed or divorced, engaging in professional technical work, chronic diseases, depression, and anxiety were risk factors for insomnia. Meanwhile, 6–12 years of education, regular dietary habits, and daily physical exercise were protective factors. For rural residents, female gender, high educational attainment, high monthly household income, chronic diseases, depression, and anxiety were risk factors, while regular diet and daily physical exercise emerged as protective factors.ConclusionInsomnia prevalence is higher among urban residents in Foshan compared to rural residents, with distinct influencing factors for each group. Findings inform tailored interventions aimed at reducing insomnia disparities across urban and rural populations.